Genetic variation in the tryptophan hydroxylase 2 gene moderates depressive symptom trajectories and remission over 8 weeks of escitalopram treatment. (May 2016) - Su, Yun-Ai; Li, Ji-Tao; Dai, Wen-Ji; Liao, Xue-Mei; Dong, Li-Cai; Lu, Tian-Lan; Bousman, Chad; Si, Tian-Mei
Abstract : The serotonin system plays an important role in the pathogenesis of major depressive disorder (MDD) and genetic variations in serotonin-related genes affect the efficacy of antidepressants. The aim of this study was to investigate the relationship between genotypic variation in six candidate serotonergic genes ( ADCY9, HTR1B, GNB3, HTR2A, TPH2, SLC6A4 ) and depressive and anxiety symptom severity trajectories as well as remission following escitalopram treatment. A total of 166 Chinese patients with MDD were treated with escitalopram (open-label) for 8 weeks. TPH2 rs4570625 GG carriers were more likely to achieve depressive and anxiety symptom remission compared with T-allele carriers. At the trend level ( P corrected =0.05), depressive symptom severity trajectories were moderated by TPH2 rs4570625. Patients with the GT or the GG genotype showed more favorable depressive symptom severity trajectories compared with TT genotype carriers. Polymorphisms in ADCY9, HTR1B, and HTR2A were nominally associated with symptom remission, but did not withstand correction for multiple comparisons. The HTTLPR polymorphism was not included in our final analysis because of a high percentage of missing data. These results suggested that genotypic variation in TPH2 may moderate the therapeutic response to esciatlopram among Chinese patients with MDD.